Case-based Learning Outperformed Simulation Exercises in Disaster Preparedness Education Among Nursing Trainees in India: A Randomized Controlled Trial. Issue 5 (5th August 2016) - Aluisio, Adam R.; Daniel, Pia; Grock, Andrew; Freedman, Joseph; Singh, Ajai; Papanagnou, Dimitrios; Arquilla, Bonnie
Abstract: Objective: In resource-constrained environments, appropriately employing triage in disaster situations is crucial. Although both case-based learning (CBL) and simulation exercises (SEs) commonly are utilized in teaching disaster preparedness to adult learners, there is no substantial evidence supporting one as a more efficacious methodology. This randomized controlled trial (RCT) evaluated the effectiveness of CBL versus SEs in addition to standard didactic instruction in knowledge attainment pertaining to disaster triage preparedness. Methods: This RCT was performed during a one-day disaster preparedness course in Lucknow, India during October 2014. Following provision of informed consent, nursing trainees were randomized to knowledge assessment after didactic teaching (control group); didactic plus CBL (Intervention Group 1); or didactic plus SE (Intervention Group 2). The educational curriculum used the topical focus of triage processes during disaster situations. Cases for the educational intervention sessions were scripted, identical between modalities, and employed structured debriefing. Trained live actors were used for SEs. After primary assessment, the groups underwent crossover to take part in the alternative educational modality and were re-assessed. Two standardized multiple-choice question batteries, encompassing key core content, were used for assessments. A sample size of 48 participants was calculated to detect a ≥20% change in mean knowledge score (α=0.05; power=80%). Robustness of randomization was evaluated using X 2, anova, and t-tests. Mean knowledge attainment scores were compared using one- and two-sample t-tests for intergroup and intragroup analyses, respectively. Results: Among 60 enrolled participants, 88.3% completed follow-up. No significant differences in participant characteristics existed between randomization arms. Mean baseline knowledge score in the control group was 43.8% (standard deviation=11.0%). Case-based learning training resulted in a significant increase in relative knowledge scores at 20.8% ( P =0.003) and 10.3% ( P =.033) in intergroup and intragroup analyses, respectively. As compared to control, SEs did not significantly alter knowledge attainment scores with an average score increase of 6.6% ( P =.396). In crossover intra-arm analysis, SEs were found to result in a 26.0% decrement in mean assessment score ( P < .001). Conclusions: Among nursing trainees assessed in this RCT, the CBL modality was superior to SEs in short-term disaster preparedness educational translation. Simulation exercises resulted in no detectable improvement in knowledge attainment in this population, suggesting that CBL may be utilized preferentially for adult learners in similar disaster training settings. AR Aluisio, P Daniel, A Grock, J Freedman, A Singh, D Papanagnou, B Arquilla .Case-based learning outperformed simulation exercises in disaster preparedness education among nursing trainees in India: a randomized controlled trial .Prehosp Disaster Med .2016 ;31 (5 ):516 –523 .